Patient Age 55 Years Old with Residual Schizophrenia with Extrapyramidal Syndrome, Hypertension and Less Family Support - Agus Indra Yudhistira Diva Putra; Kadek Riskia Megayanti; Ida Bagus Made Mahendra Wisma; Putu Aryani; Made Intan Ayurini (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2023)
Mr. IMS, 55 years old when visited at home in a mental health service program called Pusat Kesehatan Masyarakat (Puskesmas) in Denpasar city, Bali, by heteroanamnesis to his younger brother have chief complaints since six months ago did not want to take care of himself like most people. On general impression examination, the patient wore black clothes, a dark blue shirt, and long pants. The patient's hair is not combed neatly. Fingernails looked uncut and not maintained, smelled bad from the patient's body. The patient is cooperative when answering the examiner's questions and answering using Indonesian and Balinese Languages. The patient's visual contact is inadequate, one part of his eye glanced up, but the verbal contact with the examiner was sufficient, and when the patient was speaking there was a twitch under the patient's chin. The patient said his mood today when asked by the examiner was in good condition. The examiner asked the patient about the orientation and also abstract thinking and concentration the result is the normal limit.